2008
DOI: 10.1007/s11764-008-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Does talking about their relationship affect couples’ marital and psychological adjustment to lung cancer?

Abstract: Results of this study underscore the need for couple-focused interventions in lung cancer that address the communication and relationship needs of both partners. Working with couples during the initial diagnosis and treatment period and emphasizing the benefits of discussing relationship issues during this time of major upheaval may facilitate couples' successful adaptation to lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 68 publications
7
88
1
2
Order By: Relevance
“…Under such circumstances, shifting the focus away from cancer and onto the couples' relationship by talking together about it (e.g. how good it is, relationship memories and how the couple addressed challenges together in the past, and future plans) may help to remind couples of the strengths and resources that they have to deal with the disease [73,74]. Likewise, the use of humor may help couples to maintain a sense of normalcy, alleviate tensions, provide a needed distraction from emotionally laden issues, and even facilitate the discussion of difficult or sensitive topics [75].…”
Section: Other Topics Of Discussion Besides Feelingsmentioning
confidence: 99%
“…Under such circumstances, shifting the focus away from cancer and onto the couples' relationship by talking together about it (e.g. how good it is, relationship memories and how the couple addressed challenges together in the past, and future plans) may help to remind couples of the strengths and resources that they have to deal with the disease [73,74]. Likewise, the use of humor may help couples to maintain a sense of normalcy, alleviate tensions, provide a needed distraction from emotionally laden issues, and even facilitate the discussion of difficult or sensitive topics [75].…”
Section: Other Topics Of Discussion Besides Feelingsmentioning
confidence: 99%
“…108 For example, it has been demonstrated that seeing oneself as part of a couple facilitates a couples' level of cooperation 109 and minimizes the negative effects of a chronic illness on spouse mental health. 108 Badr et al 110 recently demonstrated that couples who reported engaging in more frequent discussions about their relationship within 1 month of the patient's initiation of treatment for lung cancer had greater marital adjustment and less psychologic distress up to 6 months later. Such discussions include talking about relationship memories, plans for the future, and problem solving about cancer-related issues that have impacted the relationship.…”
Section: Dyadic Level Theoriesmentioning
confidence: 99%
“…For example, scholars have documented how people's reports of Relational Uncertainty 5 the presence of relationship talk coincide with turning points (Baxter & Bullis, 1986;Bullis et al, 1993) and secret tests (Bell & Buerkel-Rothfuss, 1990). Acitelli's program of research has targeted marital satisfaction, revealing that (1) the presence of relationship talk in hypothetical scenarios is positively associated with people's perceptions of marital satisfaction (Acitelli, 1988), (2) the amount of relationship talk husbands engage in during joint interviews is positively associated with marital satisfaction for wives (Acitelli, 1992), and (3) the amount of relationship talk couples enact when one partner is suffering from chronic illness or lung cancer (Badr et al, 2008) is positively associated with their marital satisfaction. Moreover, an observational study found that dating partners perceive conversations containing prominent, in-depth, and negatively valenced relationship talk to be more consequential to their courtship .…”
Section: Theorizing About Relationship Talkmentioning
confidence: 99%
“…Second, relationship talk coincides with people's personal well-being via more contentment (Acitelli, 1992) and less depressive symptoms (Acitelli & Clair, 1996, as cited in Acitelli, 2002. Third, relationship talk corresponds with people's dyadic well-being via more relationship satisfaction Badr, Acitelli, & Taylor, 2008). Relationship talk warrants investigation, then, as a key communication process that predicts the health of individuals and relationships.…”
mentioning
confidence: 98%